First Demonstration of Thermally Stable Zr:HfO2Ferroelectrics via Inserting AlN Interlayer - Lee, Sangmok; Kim, Giuk; Lee, Sangho; Shin, Hunbeom; Lim, Youngjin; Kim, Kang; Kim, Do Hyung; Oh, Il Kwon; Ko Park, Sang Hee; Ahn, Jinho; Jeon, Sanghun (IEEE Electron Device Letters, 2024)
This letter introduces a novel methodology to improve the thermal stability of Zr:HfO2 (HZO) ferroelectric (FE) materials by adding AlN as the middle interlayer (IL) between HZO. Adding AlN to HZO improves the thermal stability of FE layers in three ways. Initially, the growth of grains and the formation of the dielectric monoclinic (m-) phase are kinetically suppressed in the HZO when subjected to a subsequent thermal budget (TB) after crystallization annealing for the formation of FE layers. The middle IL acts as a physical barrier that hinders the formation of leakage paths along grain boundaries with increasing TB. Additionally, NH3 plasma treatment during AlN deposition improves the interface quality between the IL and bottom HZO FE layer. Collectively, these beneficial effects synergistically contribute to the enhancement of thermal stability, ensuring outstanding remanent polarization (2Pr ≈ 24 μC/cm2) and reliability (≈ 4.3 x 104 cycles) even under high TB (800 °C for 30 min.). This study is a significant initial step in investigating the use of HZO FE material in 3D memory devices, which require high TB due to intricate process integration.
Keywords: 3-D integration; AlN interlayers; Ferroelectric layers; Ferroelectrics materials; Hafnia; High thermal; III-V semiconductor material; III/V semiconductors; Thermal budget; Thermally stable; 3D integration; ferroelectric; hafnia; HfZrO; thermal budget; thermal stability